2012
DOI: 10.1007/s00432-012-1319-7
|View full text |Cite
|
Sign up to set email alerts
|

KRAS p.G13D mutations are associated with sensitivity to anti-EGFR antibody treatment in colorectal cancer cell lines

Abstract: Since KRAS p.G13D-mutated tumour cells may respond to EGFR-targeted therapy, we suggest including subtype analysis of KRAS mutations in prospective clinical trials. In KRAS wild-type tumour cells, BRAF mutations and loss of EGFR or PTEN expression may lead to resistance to EGFR-targeted therapy and should be considered as additional negative predictive biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…In mCRC, as described by various authors, mutations located in codon 13 (G13D) might be associated with some response to cetuximab in pretreated patients and in patients following cetuximab-based first-line regimens. These data are supported by in vitro models of colorectal cancer [13][14]16].…”
Section: Research Articlesupporting
confidence: 54%
“…In mCRC, as described by various authors, mutations located in codon 13 (G13D) might be associated with some response to cetuximab in pretreated patients and in patients following cetuximab-based first-line regimens. These data are supported by in vitro models of colorectal cancer [13][14]16].…”
Section: Research Articlesupporting
confidence: 54%
“…Therefore, American Society of Clinical Oncology recommended cetuximab treatment for only patients with WT KRAS (21). However, there is increasing evidence showing that WT KRAS is not sufficient to confer sensitivity to cetuximab (22)(23)(24), and some patients with mutant KRAS are still sensitive to cetuximab (16,(25)(26)(27)(28). These findings suggest that further investigation into the underlying mechanisms of cetuximab resistance and identification of a better predictor for cetuximab response are ing of chemotherapeutic agents have improved the response and survival rate of colorectal patients.…”
Section: Prmt1-mediated Methylation Of the Egf Receptor Regulates Sigmentioning
confidence: 99%
“…In mCRC, the most frequently detected alterations in EGFR signalling pathways are KRAS mutations. KRAS mutations occur in approximately 30-50% of patients with mCRC [7]. Recent data suggest that KRAS mutations are negative predictors of benefit from treatment by EGFR TKIs in patients with disseminated disease [8], but these results are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…KRAS mutations have been identified in approximately 30-50% of patients with CRC [7]. In addition, several studies have indicated that the presence of mutant KRAS in lung and CRC tumours correlates with poor prognosis and is associated with a lack of response to EGFR inhibitors [8].…”
Section: Introductionmentioning
confidence: 99%